Integration of Small and Middle-Sized Enterprises into Large Energy Corporations as a Factor of Business Sustainability - Kapitonov, Ivan A.; Taspenova, Gaukhar A.; Meshkov, Vladimir R.; Shulus, Aleksei A. (International Journal of Energy Economics and Policy, 2017)
Small businesses are traditionally the driver of the economic growth in the conditions of market economy, so in the modern circumstances this thesis is seen as an axiom not requiring additional argumentation. Moreover, the role of small and middle-sized businesses in the acceleration in the rates of economic grows currently increases. The economic recession triggered by the sanctions as well as by the international collapse in oil prices, to an even greater degree actualized the task of searching the ways and methods of the Russian economy potential activation including more active and rational use of the most important nonmaterial resource of market economy that is business initiative. Keywords: Enterprises, small and middle-sized business, energy complex JEL Classifications: L53; M14; O13